2016
DOI: 10.1038/srep39383
|View full text |Cite
|
Sign up to set email alerts
|

TRPC3-GEF-H1 axis mediates pressure overload-induced cardiac fibrosis

Abstract: Structural cardiac remodeling, accompanying cytoskeletal reorganization of cardiac cells, is a major clinical outcome of diastolic heart failure. A highly local Ca2+ influx across the plasma membrane has been suggested to code signals to induce Rho GTPase-mediated fibrosis, but it is obscure how the heart specifically decodes the local Ca2+ influx as a cytoskeletal reorganizing signal under the conditions of the rhythmic Ca2+ handling required for pump function. We found that an inhibition of transient recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 31 publications
4
62
0
Order By: Relevance
“…We also found that voluntary exercise causes hypertrophy with preserved cardiac contractility by enhancing LV compliance and flexibility through destabilization of Nox2 (Figure 7, G-J, and Table 7). Taken together with our earlier observations made in a pressure-overloaded mouse heart model (20,27), our present findings, to our knowledge, provide a new concept that a TRPC3-Nox2 complex functions as a common major risk factor for chronic heart failure, driving pathological cardiac remodeling. Furthermore, they suggest that, by suppressing Nox2-mediated ROS production in cardiomyocytes, TRPC3 inhibition may be an effective strategy for reducing the risk of DOX-induced heart failure ( Figure 7K).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We also found that voluntary exercise causes hypertrophy with preserved cardiac contractility by enhancing LV compliance and flexibility through destabilization of Nox2 (Figure 7, G-J, and Table 7). Taken together with our earlier observations made in a pressure-overloaded mouse heart model (20,27), our present findings, to our knowledge, provide a new concept that a TRPC3-Nox2 complex functions as a common major risk factor for chronic heart failure, driving pathological cardiac remodeling. Furthermore, they suggest that, by suppressing Nox2-mediated ROS production in cardiomyocytes, TRPC3 inhibition may be an effective strategy for reducing the risk of DOX-induced heart failure ( Figure 7K).…”
Section: Discussionsupporting
confidence: 84%
“…In particular, two TRP canonical (TRPC) subfamily members, TRPC3 and TRPC6, reportedly participate in the development of pathological hypertrophy caused by neurohumoral factors (22,23) and mechanical stress (24)(25)(26). Our recent studies using TRPC-KO mice revealed that TRPC3, but not TRPC6, functions as a positive regulator of ROS, leading to induction of mechanical stress-induced maladaptive fibrosis (15,20,27). TRPC3 interacts with Nox2 via TRPC3-specific C-terminal sites, thereby protecting Nox2 from proteasome-dependent degradation and amplifying Ca 2+ -dependent Nox2 activation through TRPC3-mediated background Ca 2+ entry (20).…”
Section: Introductionmentioning
confidence: 99%
“…Next, we take atrial mouse fibroblasts as the cell model. Pyr-10, an selective inhibitor of TRPC3, could markedly block the DAG-mediated TRPC3 signalling pathway, controlling the extent of fibrosis in the cell models33,34 ; In our study, it was observed the lower protein levels of TRPC3 and TGF-βin Hcy+Pyr-10 group, compared to Hcy group, which implied that Pyr-10 abolished the effect of Hcy-mediated atrial fibrosis via the inhibition of DAG-TRPC3 signalling pathway. Moreover, it was attenuated Hcy-induced atrial fibrosis (Figure 5B,D) and reduced the proliferation of fibroblasts in TRPC3-shRNA-transfected fibroblasts (…”
supporting
confidence: 53%
“…TRPC3/6/7 pore complexes are able to sense various stress signals, and are primarily regulated by phospholipase C (PLC)-derived lipid mediators [6][7][8], and TRPC3 stands out for its distinct constitutive activity, which is reportedly governed by its glycosylation state [9]. TRPC3 as well as its closest relative TRPC6 have been identified to trigger Ca 2+ -dependent nuclear factor of activated T-cells (NFAT) nuclear translocation in native cardiovascular cells including myocytes [10][11][12] as well as fibroblasts [13]. Pharmacological abrogation of TRPC3/6 function was suggested as a potential therapeutic strategy for cardiovascular remodeling and heart failure prevention [14].…”
Section: Introductionmentioning
confidence: 99%